1991
DOI: 10.1093/nar/19.21.5973
|View full text |Cite
|
Sign up to set email alerts
|

Local base sequence preferences for DNA cleavage by mammalian topoisomerase II in the presence of amsacrine or teniposide

Abstract: Several classes of antitumor drugs are known to stabilize topoisomerase complexes in which the enzyme is covalently bound to a terminus of a DNA strand break. The DNA cleavage sites generally are different for each class of drugs. We have determined the DNA sequence locations of a large number of drug-stimulated cleavage sites of topoisomerase II, and find that the results provide a clue to the possible structure of the complexes and the origin of the drug-specific differences. Cleavage enhancements by VM-26 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
91
2
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 19 publications
17
91
2
1
Order By: Relevance
“…3 and Table I). This result agrees well with previous analyses (18,29). Preference on the opposite strand showed a complementary (although slightly weaker) preference for G at position ϩ5.…”
Section: Different Base Preferences Of Amsacrine-and Mitoxantronestabsupporting
confidence: 93%
See 2 more Smart Citations
“…3 and Table I). This result agrees well with previous analyses (18,29). Preference on the opposite strand showed a complementary (although slightly weaker) preference for G at position ϩ5.…”
Section: Different Base Preferences Of Amsacrine-and Mitoxantronestabsupporting
confidence: 93%
“…4 and Table I), the human enzyme showed a clear preference for A ϩ1 (47 of 64 sites) and a complementary (although weaker) preference for T ϩ4 (28 of 64 sites), which conforms with earlier studies (29,33,34). The yeast protein also demonstrated a strong preference for A ϩ1 (29 of 61 sites) but an additional preference for T at position Ϫ1 (32 of 61 sites) as well as the complementary A at position ϩ5 (28 of 61 sites), which was not seen in the human enzyme.…”
Section: Different Base Preferences Of Amsacrine-and Mitoxantronestabsupporting
confidence: 92%
See 1 more Smart Citation
“…The molecular details of this binding site are unknown, nevertheless, important information for its location have been revealed by mutational analysis of the cleavage of a preferred site for T4 topoisomerase which suggested that the drugs interact directly with the two bases on either side of the scissile phosphodiester bond (34). Similar conclusions were drawn by studying the local base sequence preference for DNA cleavage by mammalian topoisomerase II in the presence of anti-tumor drugs (35,36). In the case of gyrase, Cove et al (30) found that gyrase shows a preference for a pair of guanine bases being present on either side of the cleaved bond.…”
Section: Discussionmentioning
confidence: 78%
“…Stacking of topoisomerase poisons with the DNA base pairs immediately flanking the topoisomerase cleavage site was initially hypothesized as the mechanism of poisoning of topoisomerase II by several inhibitors of this enzyme (34)(35)(36)(37)(38). The base-stacking hypothesis has been extended to top1 poisons (camptothecins) (6,39).…”
Section: Discussionmentioning
confidence: 99%